Pengaruh Brand Ambassador Dan Brand Image Terhadap Minat Beli Produk Scarlett Whitening: (Survei Pada Konsumen Scarlett di Toko Koleksi Tasik Termurah) - Alda Alistian (CV. ULIL ALBAB CORP, 2022)
This study aims to determine the effect of brand ambassadors and brand image on buying interest in Scarlett Whitening products. The method used in this research is survey method and associative research method. The population in this study is unknown and the sample is taken as many as 100 respondents. The sampling technique used is non-probability sampling with purposive sampling method. Data collection is done through primary data and secondary data. The technique used in data collection is using a questionnaire. Based on the results of research, data processing, data analysis, and hypothesis testing with the help of SPSS 23, it shows that based on correlation analysis brand ambassadors have a moderate influence on buying interest and brand image has a strong influence on buying interest. Based on the results of the F test, brand ambassadors and brand image simultaneously have a significant effect on buying interest. Based on the t-test, brand ambassadors and brand image partially have a significant effect on buying interest.